Faktor-Faktor Penyebab Terjadinya Penolakan Suatu Klaim Nasabah Asuransi Syariah: Studi Kasus Pada Pt. Asuransi Jiwa Syariah Bumiputera - Nurdin Nasution; Atika Atika (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This research was conducted to determine the factors that cause other resistance.The research was conducted during an internship at PT. Bumiputra Sharia Life Insurance. Claims in sharia insurance are activities of providing compensation to participants who are experiencing a disaster. Claims in insurance terms are defined as requests or demands for payment of benefits in accordance with the provisions stipulated by the insurance policy. In this study the authors used qualitative methods to understand the phenomena that occur in case studies. From the research results of PT. Bumiputera Syariah Life Insurance rejects claims against customers because the case is against the law, namely the customer may make a claim but what is given is the result of the deposit while the benefits cannot be given. Whereas for those who do not meet the requirements for a claim cannot be accepted, it means that the claim submitted is rejected.